2010
DOI: 10.1038/ijo.2010.221
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of social marketing strategies to community-based obesity prevention programmes in children

Abstract: Objectives: To review child and adolescent obesity prevention programmes to determine whether they have included the Social Marketing Benchmark Criteria (BC). In addition, we analysed whether there was a relationship between the presence of the criteria and the effectiveness of the programme. Methods: Interventions had to be aimed at preventing obesity through behaviour changes relating to diet, physical activity, lifestyle and social support, separately or in combination. A total of 41 interventions were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 47 publications
0
38
0
3
Order By: Relevance
“…Although no studies have empirically assessed stigma in obesity campaigns, calls from across the globe including the United States, Australia, the United Kingdom and Canada have been made to review materials for stigmatizing content before dissemination, and to assess stigma in campaign evaluations (for example, refs. (12)(13)(14)(15)(16)(17)(18)). …”
Section: Introductionmentioning
confidence: 99%
“…Although no studies have empirically assessed stigma in obesity campaigns, calls from across the globe including the United States, Australia, the United Kingdom and Canada have been made to review materials for stigmatizing content before dissemination, and to assess stigma in campaign evaluations (for example, refs. (12)(13)(14)(15)(16)(17)(18)). …”
Section: Introductionmentioning
confidence: 99%
“…Son muchos los estudios e intervenciones que se han llevado a cabo en niños y adolescentes con el objetivo de reducir el sobrepeso y la obesidad, especialmente utilizando la AF y la dieta, tanto de forma aislada como conjunta (163,205,206 (25/27) de las intervenciones realizadas entre 1990 y 2009 fueron efectivas en producir cambios de comportamiento, como mejorar los niveles de actividad física, disminuir el tiempo y las conductas sedentarias, y cambiar comportamientos alimentarios poco saludables, como la ingesta de azúcar y de grasas. Además, casi un 61% de las intervenciones (14/23) fueron efectivas en reducir el IMC mientras que más del 87% (7/8) lo fueron para los pliegues cutáneos.…”
Section: Estrategias De Intervención Para La Prevención De La Obesidaunclassified
“…In [42], the authors studied the determinants of obesity in relation to the socio-economic status of middle-aged Swedish women, and they found that a low socio-economic status was an important factor involved in the increase of being overweight and obesity. In [71], family and social environment with high and middle-low income levels have been studied, and the authors found that there are much more fathers who are obese in middle-low income municipalities than in high income ones. However, no correlation between the income level and the BMI of the mother has been found.…”
Section: Social Factorsmentioning
confidence: 99%